Gene polymorphism associated with risk of development of homocysteine exchange disorders among young healthy women in Transbaikal kray: ethnic and reproductive aspects - T. E. Belokrinitskaya; N. I. Frolova; N. N. Strambovskaya (Acta Biomedica Scientifica, 2013)
The frequency characteristics of gene polymorphisms of MTHFR677T, MTHFR1298C, MTRRA66G that determinate folate metabolism and are associated with perinatal or pregnancy complications were studied in 50 Russian and 50 Buryatyoung healthy women of 19-27 years. The frequency of MTHFR677TT mutant genotype was 6 % (10 % among Russian, 2 % among Buryat women). MTHFR1298CC and MTRR66GG mutant genotypes were detected in 9 % and 31 % respectively without any differences between ethnic groups. Multigenic inheritance of MTHFR677TT and MTH-FR 1298CC, MTHFR677CT and MTRR66AG that multiply increase risks of miscarriage and development of defects of nervous tube of fetus were found only in the group of Russian women (2 %).